(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The demand for new technologies is usually directlyrelated to new market opportunities. Once small producers become aware of newopportunities, the challenge shifts to acquiring the capacity to supply whatthe market demands. This often requires the acquisition of new skills,management techniques, and know-how, as well as tools and equipment — allimportant aspects of technology development. Because the processes of marketdevelopment and technology mastery tend to be directly related, the primarysources of technology information, equipment, and advice and training on newproduction or processing technologies for small producers are the productbuyers and input suppliers with whom the producers interact in their normalcommercial dealings. A review of technology development and disseminationprograms reveals there is likely to be strong demand from small producers forservices that help them respond to new market opportunities and that areavailable on terms and conditions that permit them to profit from the adoptionof new technologies.